2015
DOI: 10.1021/jf5048805
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Preliminary Antibrowning Evaluations of Norartocarpetin Microemulsions

Abstract: Norartocarpetin is a flavone widely distributed in Moraceae plants with strong tyrosinase inhibitory activity. However, its poor solubility in aqueous systems and in food grade solvents (oils) limits its extensive applications. The aim of this study was to improve the solubility of norartocarpetin by developing an oil-in-water (o/w) microemulsion with food grade components. A microemulsion was developed and characterized, and its chemical and physical stabilities were also evaluated within 8 weeks. Using the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The tyrosinase inhibitory activities of isolated compounds were determined by spectrophotometric method as described in our previous study [30]. The compounds were firstly dissolved in DMSO at a concentration of 1.0 mg/mL and then diluted to different concentrations with DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…The tyrosinase inhibitory activities of isolated compounds were determined by spectrophotometric method as described in our previous study [30]. The compounds were firstly dissolved in DMSO at a concentration of 1.0 mg/mL and then diluted to different concentrations with DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Among four cosurfactants, PEG 400 has the maximum solubility values for Arto. From the above results, it was found that Tween 80 and PEG 400 had good solubility capacity for Arto, our previous study also showed that both of them exhibited good solubility capacity for norartocarpetin, a flavone (Zheng et al, 2015). These results implied that Tween 80 and PEG might be the solvents with good solubility for flavonoids.…”
Section: Solubility Study In Oils Surfactants and Cosurfactantsmentioning
confidence: 66%
“…After the components and ratio of surfactants to cosurfactants ( K m ) were optimized through pseudoternary phase diagram, the ratio of surfactants/cosurfactants mixture to oils ( K value) should be optimized by investigating the criteria, such as loading capacity, droplet size, oral safety, and stability. ,, …”
Section: Resultsmentioning
confidence: 99%
“…After the components and ratio of surfactants to cosurfactants (K m ) were optimized through pseudoternary phase diagram, the ratio of surfactants/cosurfactants mixture to oils (K value) should be optimized by investigating the criteria, such as loading capacity, droplet size, oral safety, and stability. 25,37,38 Nine blank formulations were first prepared with different K value (from K1 1:9 to K9 9:1) and optimized synergetic surfactants ratio (Tween 80/Cremophor RH40 = 1:2) and K m (K m = 2:1) (Supplemental Table 1). Phase separation was observed in K1 (1:9) and K2 (2:8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%